2007
DOI: 10.1016/j.jacc.2006.10.074
|View full text |Cite
|
Sign up to set email alerts
|

Once Daily Therapy With Isosorbide-5-Mononitrate Causes Endothelial Dysfunction in Humans

Abstract: We document for the first time that IS-5-MN impairs endothelial function in humans in vivo. Suggesting a role of oxygen free radicals, nitrate-induced abnormalities in endothelium-dependent vasomotor responses were reversed by the antioxidant vitamin C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(83 citation statements)
references
References 32 publications
2
77
0
3
Order By: Relevance
“…18,19 Recent studies have demonstrated that chronic administration of nitrates induces endothelial dysfunction. 20, 21 The present study showed that long-term nitrate treatment is significantly independently associated with cardiac events in VSA patients. Long-term nitrate treatment might cause nitrate tolerance, thus leading to subsequent endothelial dysfunction.…”
Section: -18supporting
confidence: 53%
See 1 more Smart Citation
“…18,19 Recent studies have demonstrated that chronic administration of nitrates induces endothelial dysfunction. 20, 21 The present study showed that long-term nitrate treatment is significantly independently associated with cardiac events in VSA patients. Long-term nitrate treatment might cause nitrate tolerance, thus leading to subsequent endothelial dysfunction.…”
Section: -18supporting
confidence: 53%
“…Long-term ISMN treatment, even on a once-daily use, might therefore not be beneficial for preventing nitrate tolerance or preventing endothelial dysfunction. 21 CCBs are widely used medications in the management of VSA, and a recent guideline for the diagnosis and treatment of VSA recommended CCBs as first-line agents for VSA patients. 1 Short-acting nitrates are recommended only for sublingual administration, spraying in the oral cavity, or intravenous administration during an anginal attack.…”
Section: Effects Of Medications On Cardiac Events In Vsa Patientsmentioning
confidence: 99%
“…26, 28 Isosorbide mononitrate with 1 −ONO2 was found to induce the development of moderate nitrate tolerance, despite suppression of vascular superoxide production. 27 Coadministration of angiotensin-converting enzyme inhibitors has been reported to improve endothelial dysfunction, but not to improve nitrate tolerance. 15, 29 Intermittent administration of organic nitrates with nitrate-free intervals has been demonstrated to avoid tolerance, but with several disadvantages, including lack of protection against angina and rebound ischemia during or after the nitrate-free periods.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term use of nitrates has been implicated to cause endothelial dysfunction both by oxygen free radical mediated abnormalities in endothelium-dependent vasomotor responses and by inhibition and down regulation of vascular aldehyde dehydrogenase (ALDH-2). 21,22 Nicardipine has been used prophylactically as an intragraft infusion to prevent no-reflow in patients undergoing elective SVG-saphenous venous graft. 23 Unlike studies with other vasodilators such as intravenous potassium channel activator, nicorandil, 24 intracoronary verapamil, 25 and adenosine, 26 pretreatment with intracoronary nicardipine in patients undergoing elective PCI showed no statistically significant benefit in our study.…”
Section: Discussionmentioning
confidence: 99%